The Vascular Impairment of Cognition Classification Consensus Study. Issue 6 (10th December 2016) - Skrobot, Olivia A.; O'Brien, John; Black, Sandra; Chen, Christopher; DeCarli, Charles; Erkinjuntti, Timo; Ford, Gary A.; Kalaria, Rajesh N.; Pantoni, Leonardo; Pasquier, Florence; Roman, Gustavo C.; Wallin, Anders; et al.
Abstract: Introduction: Numerous diagnostic criteria have tried to tackle the variability in clinical manifestations and problematic diagnosis of vascular cognitive impairment (VCI) but none have been universally accepted. These criteria have not been readily comparable, impacting on clinical diagnosis rates and in turn prevalence estimates, research, and treatment. Methods: The Vascular Impairment of Cognition Classification Consensus Study (VICCCS) involved participants (81% academic researchers) from 27 countries in an online Delphi consensus study. Participants reviewed previously proposed concepts to develop new guidelines. Results: VICCCS had a mean of 122 (98–153) respondents across the study and a 67% threshold to represent consensus. VICCCS redefined VCI including classification of mild and major forms of VCI and subtypes. It proposes new standardized VCI‐associated terminology and future research priorities to address gaps in current knowledge. Discussion: VICCCS proposes a consensus‐based updated conceptualization of VCI intended to facilitate standardization in research.